Mídia e a produção discursiva de novas identidades femininas na pós-modernidade - Britto, Patrícia Duarte de (2008)
The theme of current research comprises the process of the identity status of the female subject in the discourses of contemporary social mass media. The printed past-time magazine published for the female population is highlighted. Research deals with the manner knowledge on the female population, or rather, the necessary "truths" for the formation of feminine identities, is built. The relationships between knowledge, economic and social processes, types of behavior, system of norms and techniques are established so that the new post-modern woman may be understood, coupled to what she says she is and what the social mass media say she is. The dissertation is foregrounded on the intercrossing between language, society, history and memory. The theoretical and analytic basis is made up of studies on the third wave of Michel Pêcheux's Discourse Analysis, Jean-Jacques Courtine's discourse formulas and chiefly on Michel Foucault's contributions to the theory of discourse. It is also based on research on Mass Communication Theory and on Cultural Studies as from the displacements underlying the suppositions of post-modernism. Foucault's archeological method leads us on our analyses guided by the key concepts of enunciation, enunciation function, discursive regularity, archive, governmentability, discursive memory, interdiscourse, thematic path, mass communication, identity, difference and post-modernity/net modernity, elastic woman, fragmentation and fluctuation. Analytic material is composed of ten reports withdrawn of four numbers of the Brazilian magazine Veja Edição Especial Mulher, published in August 2002, August 2003, May 2006 and June 2008. The above-mentioned material was organized according to three thematic trajectories from which the construction of new feminine identities in post-modernity could be detected: a) jobs, women and their multiple roles; b) female aesthetic beauty; c) love relationships between the male and the female. A set of verbal enunciations, actually said by women, are analyzed. These women make themselves subjects through a relationship constituted by special types of agency and self-control by which they understand what they are and built up an identity of their own. As a matter of fact, they make themselves the subjects of their own existence. Verbal enunciations prepared by knowledge holders hailing from different stances are also investigated. The organization of the enunciations by the magazine editors favors the construction of model images, the legitimization of multiple collective identities and the determination of types of behavior with the aim at producing feminine subjects. The hypothesis of current dissertation, confirmed by results of research, is that the magazine Veja is not merely an institutional control tool that fabricates behavior, ideas and ways of thinking. Neither is it a merely mentor that exercises certain authority for the control of the female readers' roles. Actually, Edição Especial Mulher is mainly a place where the contemporary woman, as a living being, inscribes its day-to-day experience in each page, experiences her own practices, techniques, behavior and discipline programs. Whereas in certain instances she submits herself to the magazine's dictum, at others she frees herself from it when she makes herself a subject and is conscious of her own condition. Definite answers are not given. Techniques and the processes that make up history, construct discourses and constitute new feminine identities have been diagnosed in magazines. Current research, therefore, lies within the reflection condition, without any presumption of definitely solving the issue. In fact, the archive exists to be explored for new approaches.